PENGARUH MODEL PEMBELAJARAN JIGSAW BERBANTUAN MEDIA PUZZLE TERHADAP HASIL BELAJAR PAS KELAS IV - Dela Sucitra; Husna Parluhutan Tambunan; Sorta Simanjuntak; Khairul Usman; Putra Afriadi (Universitas Negeri Medan, 2024)
The research was carried out with the aim of developing Student Worksheets (LKPD) so as to produce LKPD products based on the index card match learning model for Indonesian class I, describing the feasibility of LKPD based on the index card match learning model for Indonesian class I. This research used the Research and Development method (R&D) using the ADDIE model. In the ADDIE model research, there are 4 stages of research carried out, namely Analysis, Design, Development, Implementation, and Evaluation. The results of this research are that a Student Worksheet (LKPD) product based on the index card match Indonesian language learning model for class I has been produced with an average feasibility score of 91.66% from material experts and in the very feasible category, 86.15% from experts. design and included in the very feasible category, 92% of educational practitioners and included in the very feasible category. So it can be concluded that the Student Worksheet (LKPD) product based on the class I Indonesian index card match learning model is suitable for use as additional teaching material in schools, especially class I.